Training Curriculum Development of Classroom Action Research along with the Sufficiency Economy Philosophy - Naowanich, Ekachai (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2018)
The main purpose of this research was to develop classroom action research including the Sufficiency Economy Philosophy for instructors at Rajamangala University of Technology Suvarnabhumi. There were 4 steps as follows: 1) The fundamental study. 2) The curriculum design for instructors as classroom action research along with the Sufficiency Economy Philosophy. The curriculum draft was evaluated by experts. Its appropriation was at a moderate level. The Index of Objective items Congruence was in agreement with the curriculum components. 3) Implement ation of the curriculum as classroom action research along with the Sufficiency Economy Philosophy at Rajamangala University of Technology Suvarnabhumi. From self-assessment by the participants, most of them had never done any research (90.91%) and had few classroom action research fundamentals at a low level (36.36%). The satisfaction toward the curriculum was high in regard to both the content and training. 4). The curriculum evaluation and revision led to revising and developing the curriculum for instructors as classroom action research along with the Sufficiency Economy Philosophy at Rajamangala University of Technology Suvarnabhumi and could be applied for instruction development.